PROMOSI CAMILAN NORI BAGI ANAK DAN REMAJA DI KELURAHAN HATIVE KECIL. - Lalopua, Vonda M. N.; Noya, Erin D. (Balobe: Jurnal Pengabdian Masyarakat, 2025)
One of the food products derived from seaweed is nori, a healthy snack rich in nutrients. Nori products are imported and sold in large supermarkets, making local seaweed nori less well-known to the community. The purpose of this Community Service Program (PKM) is to promote seaweed nori snacks to children and adolescents in Hative Kecil Village, Sirimau District, Ambon City. The expected benefit of this PKM is that seaweed nori products become one of the preferred healthy and nutritious snack options in the community. The PKM implementation uses a lecture method with media in the form of leaflets, organoleptic assessment sheets, and nori products. The lecture provides education about seaweed nori products, including types and variants, nutritional value, purchase locations, and prices. The results of the PKM show that Tae kae noi and nori mamasuka snacks can be accepted by children and adolescents in Hative Kecil Village. Elementary school children gave a fairly positive response because they were introduced to nori products for the first time. Adolescents gave a very positive response to nori products because they had previously purchased nori. The preference for nori depends on attractive packaging and nori variants with specific flavors, aromas, textures, and nutritional values.